2022-RA-1664-ESGO Consensus radiotherapy guidelines vulvar cancer: Spanish GINECOR/SEOR group modified Delphi study. (20th October 2022) - Largo, Sofia Cordoba; Rodriguez, Isabel; Latorre, Javier Anchuelo; Jamal, Dina Najjari; Villalba, Silvia Rodriguez; Fuente, Cristina de la; Álvarez, Francisco Celada; Cabezas, Sonia García; Belda, María Sanchez; Iturre, Elena Villafranca; Olmeda, Belen Belinchon; Paniagua, Luz Couselo; et al.
Abstract : Introduction/Background: Due to the low incidence of vulvar cancer, there are very few randomized studies for decision making in these patients. Current recommendations are mostly based on retrospective studies and institutional experience. The present consensus was developed by a team of spanish radiation oncologists on behalf of the subgroup GINECOR of the Spanish Society of Radiation Oncology, (SEOR) to provide a current review of the radiation treatment of vulvar cancer (VC). Methodology: A national panel of experts were recruited to reach consensus on the radiation treatment of VC. Prior to the discussion of the statements, we performed an extensive analysis of current medical literature from peer-reviewed journal to define evidence-based treatment options. A 2-round web-based modified Delphi study was conducted to reach a consensus on the appropriateness of the different therapeutic options in each clinical setting. The appropriateness of various therapies was classified as strongly agree, agree, neither agree nor disagree, disagree, strongly disagree. In those instances where evidence is lacking or not definitive, expert opinion was used to formulate recommendations. Results: Recommendations are made for using radiotherapy focused on the indications of radiotherapy. Three clinical scenarios were defined: adjuvant treatment, locally advanced vulvar cancer and recurrent disease. A high level of agreement over 80% was reached. Adjuvant radiotherapy is recommended for resected vulvar carcinoma with adverse risk factors, mainly positive margins and lymph nodes. For patients with unresectable vulvar carcinoma EBRT with or without chemotherapy should be considered. The approach to a recurrence of vulvar carcinoma must be individualized for each patient in different clinical scenarios Conclusion: In those aspects of vulvar cancer where evidence is not definitive, expert panel consensous may help in clinical decision-making